Modeling of an Oscillating Wave Surge Converter With Dielectric Elastomer Power Take-Off - Moretti, Giacomo; Forehand, David; Ingram, David; VERTECHY, ROCCO; FONTANA, Marco (Volume 9A: Ocean Renewable Energy, 2014)
This paper introduces a novel concept of Oscillating Wave Surge Converter, named Poly-Surge, provided with a Dielectric Elastomer Generator (DEG) as Power Take-Off (PTO) system. DEGs are transducers that employ rubber-like polymers to conceive deformable membrane capacitors capable of directly converting mechanical energy into electricity. In particular, a Parallelogram Shaped DEG is considered. In the paper, a description of the Poly-Surge is outlined and engineering considerations about the operation and control of the device are presented. In addition, a mathematical model of the system is provided. Linear time-domain hydrodynamics is assumed for the primary interface, while a non linear electro-hyperelastic model is employed for the DEG PTO. A design approach for the Poly-Surge DEG PTO is introduced which aims at maximizing the energy produced in a year by the device in a reference wave climate, defined by a set of equivalent monochromatic wave conditions. A comparison is done with two other WEC models that employ the same primary interface but are equipped with mathematically linear PTO systems under optimal and suboptimal control. The results show promising performance of annual energy productivity, with slightly reduced values for the Poly-Surge, even if a very basic architecture and control strategy are assumed.